More Aroused, Less Fatigued: Fatty Acid Amide Hydrolase Gene Polymorphisms Influence Acute Response to Amphetamine - Dlugos, Andrea M (Nature Publishing Group, 2010)
Amphetamine is a stimulant drug that enhances attention and feelings of alertness. Amphetamine's effects are known to be modulated by endogenous cannabinoids, which are degraded by the enzyme fatty acid amide hydrolase (FAAH). In this study we investigated inter-individual differences in mood response to amphetamine in relation to four polymorphisms in the FAAH gene, including the FAAH missense variant rs324420C → A (Pro129Thr), which was previously found to be associated with street drug use and addictive traits. One hundred and fifty-nine healthy Caucasian volunteers participated in a three-session, double-blind crossover study receiving either placebo or oral d-amphetamine (10 and 20 mg). Associations between individual genotypes and levels of self-reported Arousal (Profile of Mood States) after d-amphetamine ingestion were investigated using two-way ANOVAs/ANCOVAs. Association analyses for haplotypes were performed using the adaptive permutation approach implemented in PLINK. Genotypes at rs3766246 and rs2295633 were significantly associated with increased ratings of Arousal (p<0.05) and Fatigue (p<0.01) after the 10-mg dose. Fatigue levels were also found to be associated with the haplotypes CCC and TAT formed from rs3766246, rs324420, and rs2295633 (p<0.05). These data suggest that the endocannabinoid system influences variation in subjective response to amphetamine. This has important implications for understanding the role of endogenous cannabinoids in response to amphetamine, studies of poly-substance abuse, and understanding the genetic determinants of inter-individual differences in stimulant effects and risk of abuse.